High Yield Pedagogy and FOAM as Dynamic Drivers of Building Human Capital and Successful Pandemic Rapid Responses in a Low Middle Income Country. (March 2022) - Smith, S.; Seepersaud, M.; Marrero, A.; Davidson, T.
Abstract : Purpose: We hypothesized that utilizing a High Yield Pedagogy Model of our own design would result in a successful self-sufficient pandemic response capacity in a Resource Limited Environment by promoting rapid upscaling of skilled clinician-educators and complex knowledge translation into clinical practice. Methods & Materials: In response to the eruption of SARS-CoV2 in Guyana, which resulted in a surge of patients combined with a paucity of trained Critical-Care Medicine / Pulmonology Providers, we developed a blended learning Mechanical Ventilation course to rapidly upscale Human Capital and Critical-Care Medicine capacity. Our course primarily utilizes U.S. Special Operations Medicine Force Multiplier Train the Trainer strategies combined with a dynamic flipped classroom High Yield Pedagogy approach based in cognitive neuroscience to optimize rapid knowledge acquisition, retention and translation into clinical practice. We incorporated two on-line Free Open Access Meducation (FOAM) resources (one purely didactic and the other a ventilator simulator), several novel self-study clinical scenarios that dynamically progressed in tandem with assigned learning, and we culminated with an in person clinician-student driven intensive scenario based training (SBT) exercise in which each student was not only required to present a variety of complex cases, but also to effectively conduct training in an environment emphasizing Psychological Safety, Dynamic Process Improvement and a continuum of 360 degree feedback mechanisms. Results: Our High Yield Pedagogy model rapidly and successfully produced a sustainable and self-sufficient Critical-Care Medicine Capacity. We were able to provide comprehensive just in time, turnkey SARS-CoV2 Mechanical Ventilation didactic and clinical training for Guyana's Ministry of Health, which in turn allowed them to dynamically pivot, rapidly upscale human capital, and successfully manage their initial surge of COVID-19 patients. Conclusion: High Yield Pedagogy with a focus on sustainable self-sufficiency utilizing a flipped classroom, FOAM, and Psychological Safety is an effective mechanism to promote rapid knowledge translation and upscaling to increase critical-care capacity and optimize complex clinical outcomes under pandemic surge conditions in Low Middle Income Countries and severely Resource Limited Environments.